2022
DOI: 10.1007/s10508-022-02298-4
|View full text |Cite
|
Sign up to set email alerts
|

Sex in the Time of COVID-19: Patterns of Sexual Behavior Among LGBTQ+ Individuals in the U.S.

Abstract: The SARS-CoV-2 virus, the pathogen which causes COVID-19, has left an indelible impact on the daily lives of individuals in the USA. This study sought to explore the sexual behaviors among people in the LGBTQ+ population at the onset of the pandemic. Behaviors were explored across sub-groups of the population. The study employed data from an internet survey about the impact of COVID-19 on LGBTQ+ identified individuals conducted between May and July 2020. The final sample was comprised of 1090 participants from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
1
6
1
Order By: Relevance
“…Results of this study can help inform the development and tailoring of monkeypox prevention strategies geared towards these populations. Similar to work conducted during the early days of the COVID-19 pandemic (Corneli et al, 2022 ; Griffin et al, 2022 ; McKay et al, 2021 ; Starks et al, 2022 ; Stephenson et al, 2021 ; Walsh et al, 2021 ), our results demonstrate that MSM and transgender women employ a variety of exposure mitigation strategies currently endorsed by the CDC ( 2022e ). This includes limiting their exposure by avoiding crowded social venues where close, personal, skin-to-skin contact is likely to occur—such as a party, dance club, or sex club where minimal clothing may be worn.…”
Section: Discussionsupporting
confidence: 85%
“…Results of this study can help inform the development and tailoring of monkeypox prevention strategies geared towards these populations. Similar to work conducted during the early days of the COVID-19 pandemic (Corneli et al, 2022 ; Griffin et al, 2022 ; McKay et al, 2021 ; Starks et al, 2022 ; Stephenson et al, 2021 ; Walsh et al, 2021 ), our results demonstrate that MSM and transgender women employ a variety of exposure mitigation strategies currently endorsed by the CDC ( 2022e ). This includes limiting their exposure by avoiding crowded social venues where close, personal, skin-to-skin contact is likely to occur—such as a party, dance club, or sex club where minimal clothing may be worn.…”
Section: Discussionsupporting
confidence: 85%
“…Although some studies declare decreasing trend in sexual desire and intercourse at the same time (Fuchs et al, 2020; Li et al, 2020), few findings in opposing ways show more frequent intercourse and growing sexual desire (Fuchs et al, 2020; Yuksel & Ozgor, 2020). Finally, however, our study demonstrated the number of partners has not significantly changed during these periods, Griffin et al stated LGBTQ+ population in the United States chose fewer partners and lesser sexual activity during the pandemic compared with before (Griffin et al, 2022).…”
Section: Discussioncontrasting
confidence: 56%
“…Several studies suggest that HIV transmission may have been reduced by the decrease in sexual interactions with casual partners due to the restriction of physical and social contacts during the periods of strict confinement [ 11 ]. An online survey among MSM in Belgium showed a sharp drop in the number of casual sex partners during the first lock-down period from March to May 2020 [ 12 ].…”
Section: Discussionmentioning
confidence: 99%